Efficacy and Toxicity of Amphotericin B-Chitosan Nanoparticles in Mice with Induced Systemic Candidiasis - Limpeanchob, Nanteetip; Tiyaboonchai, Waree; Lamlertthon, Supaporn; Viyoch, Jarupa; Jaipan, Somkiet (Asian Health, Science and Technology Reports, 2006)
Amphotericin B (AmB) is one of the most widely used agents for treating systemic fungal infections. Although AmB is available as a colloidal dispersion with sodium deoxycholate (Fungizone®), its use is limited by renal toxicity. The goal of the present study was to evaluate the therapeutic activity and toxicity of a newly developed formulation, AmB chitosan nanoparticles (AmB-Chi nanoparticles), compared to Fungizone®. The in vitro antifungal activity was determined by measuring the growth inhibitory effect against Candida albicans and the in vivo antifungal activity was studied in mice with systemic candidiasis induced by C. albicans. The results demonstrate that both formulations showed no difference in their antifungal activity. The toxicity of both formulations was also investigated. In comparison with Fungizone® , AmB-Chi nanoparticles showed the same degree of toxicity but a slower progression of the acute toxicity and hence a reduced mortality rate. Amphotericin B chitosan particles showed less renal toxicity compared to the commercially available AmB formulation. The results suggest that AmB nanoparticles using chitosan as a carrier maintain their antifungal activity but are less toxic especially with respect to the renal toxicity compared to AmB-deoxycholate. Empty chitosan nanoparticles were also given to candidiasis compromised mice. They also showed a reduction of the mortality rate of the mice most probably due to binding of candida to the polymer resulting in a reduced activity and toxicity. The results of this study indicate that AmB-Chi nanoparticles have the potential to become a suitable drug delivery system for AmB, but more work is needed for reduction of the particle size of the carrier in order to increase its efficacy and decrease its side effects.